The Role of Sharia Micro Financing in the Development of Micro Small and Medium Enterprises in Telanaipura District - Wicaksono, Agung; Anita, Efni; Rahma, Sri; Nasrullah, Aditya; Nikmah, Isnadiatun; Rusmiyati, Mellyani (International Journal of Economics (IJEC), 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important part of the economy of a country or region, including Indonesia. The development of the MSME sector provides its own meaning in efforts to increase economic growth and in efforts to reduce the poverty rate in a country. The role of sharia microfinance plays an important role in business development for MSMEs. The aim is to find out whether MSME actors have run their businesses using sharia microfinancing and what role sharia microfinance plays in business development for these MSME actors. This research is field research using qualitative methods. Data collection techniques using observation, interviews and documentation. The interview this time consisted of several MSME actors in the Telanaipura District, Jambi City. The results of this research are MSME actors in Telanaipura District who have run their businesses by carrying out sharia micro financing and the important role of sharia micro financing in business development for these MSME actors.